2006
DOI: 10.2139/ssrn.934796
|View full text |Cite
|
Sign up to set email alerts
|

Services Liberalization in the New Generation of Preferential Trade Agreements (PTAs): How Much Further than the GATS?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 10 publications
(1 reference statement)
0
36
0
1
Order By: Relevance
“…Such an analysis can be found in Stephenson (2002) and recently in Roy et al (2006) and Fink and Molinuevo (2007).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Such an analysis can be found in Stephenson (2002) and recently in Roy et al (2006) and Fink and Molinuevo (2007).…”
mentioning
confidence: 73%
“…63. Roy et al (2006) analyse commitments undertaken by 29 WTO Members under mode 1 and mode 3 in 28 RTAs at the level of the 152 sub-sectors (for mode 3) of the W/120 Classification List. For each country and each RTA, they report the proportion of sub-sectors where commitments are made.…”
mentioning
confidence: 99%
“…As in the case of goods, we confirm that GATS commitments have been greatest for the HICs. Next we examine commitments at the bilateral level through commitments made during RTAs by taking inspiration from the recent literature on services liberalization through RTAs (Roy et al, 2006;Miroudot et al, 2010 To measure GATS commitments, we use an Environmental Service Liberalization (ESL) index adapted from Miroudot et al (2013) to reflect better the importance of different services and modes of delivery for environmental services. The ESL index gives scores and weighs scores by mode at the sub-sector level (155 sub-sectors).…”
Section: Environmental Services: Do Rtas Reduce Trade Barriers In Envmentioning
confidence: 99%
“…A comprehensive survey of provisions on services in recent PTAs found that the United States consistently obtained better commitments from its partners than did other countries that concluded PTAs with the same partners (Roy, Marchetti and Lim 2007).…”
Section: Who Concedes Most?mentioning
confidence: 99%